2019
DOI: 10.1111/jan.14213
|View full text |Cite
|
Sign up to set email alerts
|

Battle weary/battle ready: A phenomenological study of parents' lived experiences caring for children with autism and their safety concerns

Abstract: Aim:The first aim of this study was to explore the lived experiences of parents caring for their autistic children and their experiences with safety for these children.The second aim was to elicit safety recommendations from the parents of autistic children.Design: Hermeneutic phenomenology. Methods:Fifteen participants who self-reported they were parents of children with autism were recruited via snowball sampling. Data were collected from September 2017-December 2018 in audiotaped interviews using semi-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This need was corroborated in Hock et al (2012), Hurlbutt (2011), and Moodie-Dyer et al (2014), where couples noted one parent decided to end their career to take care of their child with ASD. Parents in Celia et al (2020) and Schaaf et al (2011) described the need to transition into a constant hypervigilant state of alertness to protect their children with ASD, including physical modification of their houses to prevent elopement and other dangers. Lloyd et al (2019) noted that 38% of parents in their study experienced extreme difficulty in completing daily routine activities due to the unpredictable nature of ASD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This need was corroborated in Hock et al (2012), Hurlbutt (2011), and Moodie-Dyer et al (2014), where couples noted one parent decided to end their career to take care of their child with ASD. Parents in Celia et al (2020) and Schaaf et al (2011) described the need to transition into a constant hypervigilant state of alertness to protect their children with ASD, including physical modification of their houses to prevent elopement and other dangers. Lloyd et al (2019) noted that 38% of parents in their study experienced extreme difficulty in completing daily routine activities due to the unpredictable nature of ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Parents frequently experienced stigma from relatives, friends, and strangers in the community. Celia et al (2020) and Neely-Barnes et al (2011) observed that, because ASD does not have phenotypic manifestations, a child with ASD who is having trouble in public is often assumed by outsiders to be a misbehaving child, with social repercussions for both the child and parents. One 16-year-old sibling with cerebral palsy in Neely-Barnes et al (2011) noted that other people are more cruel to her 12-year-old brother with ASD than to her because they misinterpret his ASD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 59% of the participants believed that the family members of children with ASD do not experience psychological problems (Table 2). However, it has been found that the family members and caregivers of children with autism experience psychological problems such as depression, fear, uncertainty, and guilt 32–36 . Chronic diseases lower quality of life by increasing care burden 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common sources of stress expressed by parents include child behavior and development, etiology of ASD, nancial costs, family relationships, uncertainty with the future, and autism-related services (Hall and Graff 2010;Tehee et al 2009). Parents and caregivers often report feeling felt misunderstood by others, including healthcare providers and family members (Celia et al 2020). Mothers have reported spending signi cantly more time caring for their autistic children, feeling more fatigued, and experiencing twice as many days with stress compared to mothers of children without ASD (Smith et al 2010).…”
Section: Introductionmentioning
confidence: 99%